Adaptive frequency deviation improvement using a voltage-controlled storage inverter in a weak distribution network with a high penetration level of stochastic photovoltaic power - Li, Zhicheng; Chen, Jinyu; Zhang, Weijun; Chen, Dawei; Zhang, Shuling; Gao, Tongtong; Zhang, Wei; Wang, Zhenxiong (Frontiers in Energy Research, 2023)
With the rapid increase in the use of renewable energy sources, the strength of the power grid is reduced, which may lead to many weak distribution networks. The inertia of the weak distribution network decreases significantly, which leads to poor voltage quality. It means that the voltage and frequency are distorted and deviated. Battery storage can balance the frequent power disturbance and improve the frequency quality. However, it usually requires a central controller to dispatch the power in the current-controlled mode or respond natively with a fixed linear curve in voltage-controlled mode. The performance is poor when the power demand is in a wide range, which further deteriorates the frequency quality. To solve this problem, this paper proposes an adaptive frequency deviation improvement method for energy storage in the voltage-controlled mode. This method can change the power output characteristics of the storage inverter according to the magnitude and trend of power demand, where both frequency deviation and changing rate are used to shape the output power curve. A transfer function model for a voltage-controlled storage inverter is set up for theoretical analysis. Then, with the model, an adaptive frequency deviation improvement method is proposed with a fast response to power demand in a wide range. Finally, the results verify the effectiveness of the proposed method for frequency quality improvement with a high penetration level of stochastic photovoltaic power.